Species of the family Nemouridae (Plecoptera) from Taihang Mountains of Northern China, with description of Nemoura taihangshana sp. n. - Wang, Hongliang; Li, Weihai; Yang, Ding (Zootaxa, 2013)
A distinctive new species of the genus Nemoura is described from the Taihang Mountains of northern China, N. taihang-shana. The new species is compared with similar species. Amphinemura sinensis (Wu, 1926) is redescribed and the first record of N. geei Wu, 1929 from Henan Province is also given.